Monte Carlo and analytical calculation of lateral deflection of proton beams in homogeneous targets - Pazianotto, Maurício T. [UNESP]; Inocente, Guilherme F. [UNESP]; Da Silva, Danilo Anacleto A. [UNESP]; Hormaza, Joel M. [UNESP] (AIP Publishing, 2010)
Proton radiation therapy is a precise form of radiation therapy, but the avoidance of damage to critical normal tissues and the prevention of geographical tumor misses require accurate knowledge of the dose delivered to the patient and the verification of his position demand a precise imaging technique. In proton therapy facilities, the X-ray Computed Tomography (xCT) is the preferred technique for the planning treatment of patients. This situation has been changing nowadays with the development of proton accelerators for health care and the increase in the number of treated patients. In fact, protons could be more efficient than xCT for this task. One essential difficulty in pCT image reconstruction systems came from the scattering of the protons inside the target due to the numerous small-angle deflections by nuclear Coulomb fields. The purpose of this study is the comparison of an analytical formulation for the determination of beam lateral deflection, based on Molière's theory and Rutherford scattering with Monte Carlo calculations by SRIM 2008 and MCNPX codes. © 2010 American Institute of Physics.
Keywords: Lateral Deflection; Monte Carlo; Protontherapy